2022
DOI: 10.12998/wjcc.v10.i11.3321
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging specific biomarkers-based therapeutic strategies for hepatocellular carcinoma

Abstract: The prevention, early discovery and effective treatment of patients with hepatocellular carcinoma (HCC) remain a global medical challenge. At present, HCC is still mainly treated by surgery, supplemented by vascular embolization, radio frequency, radiotherapy, chemotherapy and biotherapy. The application of multikinase inhibitor sorafenib, chimeric antigen receptor T cells, or PD-1/PD-L1 inhibitors can prolong the median survival of HCC patients. However, the treatment efficacy is still unsatisfactory due to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
(99 reference statements)
0
0
0
Order By: Relevance
“…Studies of the mechanisms by which GPC3 promotes HCC progression have shown that GPC3 functions by binding to molecules such as the Wnt/β-catenin signaling or growth factors in hepatocarcinogenesis[ 14 , 72 ]. In addition, because of the specificity of GPC3 for HCC, serum GPC3 detection has been used in the diagnosis, prognosis and molecular targeted therapy of liver cancer[ 73 , 74 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the mechanisms by which GPC3 promotes HCC progression have shown that GPC3 functions by binding to molecules such as the Wnt/β-catenin signaling or growth factors in hepatocarcinogenesis[ 14 , 72 ]. In addition, because of the specificity of GPC3 for HCC, serum GPC3 detection has been used in the diagnosis, prognosis and molecular targeted therapy of liver cancer[ 73 , 74 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%
“…Many kinds of specific signalling molecules in malignantly transformed hepatocytes can be expressed in liver tissues and secreted into the circulating blood during the occurrence, development and progression of hepatocarcinogenesis[ 12 , 13 ]. Upregulating signals at the early stage of HCC can not only elucidate the underlying mechanisms but also lay a foundation for early monitoring and future targeted therapy for HCC[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation